The pathogenic role of tubulin tyrosine ligase and D2 tubulin in Alzheimer's disease. (1st February 2022) - Parato, Julie; Kumar, Atul; Pero, Maria Elena; Qu, Xiaoyi; Ramírez, Marian Blanca; Sproul, Andrew; Bartolini, Francesca
Abstract: Background: Neurons possess both stable and dynamic microtubules (MTs), and regulation of the balance between these two states is critical to avoid disease. Post‐translational modifications (PTMs) of tubulin can alter MT stability. We have preliminary evidence indicating that premature MT longevity and accumulation of D2 tubulin, a tubulin PTM associated with long‐lived and hyperstable MTs, play a pathogenic role in AD. D2 tubulin is derived from the cleavage of the last two residues of alpha‐tubulin by the sequential actions of VASH1/2 and the CCP family of tubulin carboxypeptidases. De‐tyrosinated tubulin, lacking just one terminal residue, can be returned to its original, tyrosinated state by TTL, a rate‐limiting enzyme. Method: Immunoblot analyses of TTL and D2 levels were carried out on frozen human hippocampal tissue. Western blot and microtubule dynamics experiments were performed on human cortical neurons derived from iPSC lines in which the London familial APP mutation V717I was knocked into one allele of the IMR90 control backbone using CRISPR/Cas9 technology to mimic fAD. Lentiviral infection with cDNA shRNA against TTL was used on primary rat hippocampal cultures. Spine density and morphology was quantified by DioListic labelling prior to imaging and reconstruction. Result: We found that levels of TTL were decreased in lysates from AD brains compared to age‐matched controls and that, in contrast, D2 tubulin was significantly higher in the AD brains. In the APP London cortical neurons, which accumulate amyloid beta(1‐42) and hyperphosphorylated tau in an age‐dependent manner, TTL levels again decreased while D2 tubulin increased. We examined whether these changes correlated with an increase in MT stability by measuring MT dynamics and found that in the APP London line, dynamic MTs demonstrated decreased catastrophe frequency and longer comet lifetimes, conditions that are compatible with MT hyperstabilization. We found that depletion of TTL expression in rat hippocampal cells promoted accumulation of D2 tubulin and caused dendritic spine loss. Conclusion: Together, our results indicate that loss of TTL and accompanying accumulation of D2 tubulin are hallmarks of both sporadic and familial AD and that loss of MT dynamicity is a feature of familial AD that may contribute to synapse loss and disease progression.